Revision of the Holarctic genus Novakia Strobl (Diptera: Mycetophilidae) - Kerr, Peter H. (Zootaxa, 2007)
Two new species of fungus gnats (Diptera: Mycetophilidae), Novakia miloi and Novakia lisae spp. nov., are described and figured from California. Novakia distincta Fisher is transferred to Tetragoneura Winnertz and a replacement name, Tetragoneura fisherae Kerr, nom. nov., is given for this species. A diagnosis and description of the genus Novakia Strobl is presented and includes a key to species of the genus. The relationship of species within the genus Novakia is briefly discussed.